Determination of Bank Financial Stability in Indonesia: An Analysis of Liquidity Creation, Profitability, and Credit Risk - Sukarianto, Nanda Arifah; Pangestuty, Farah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The resilience of the banking system is a fundamental prerequisite for maintaining financial system stability, especially amid increasing global pressures in the wake of the pandemic and geopolitical conflicts. This study aims to examine the factors influencing bank financial stability in Indonesia, highlighting the roles of liquidity creation (LC), profitability measured by return on equity (ROE), and credit risk, proxied by the non-performing loan (NPL) ratio. Bank financial stability in this study is measured using the Z-Score, based on quarterly panel data from four KBMI IV banks from 2020 to 2024. The analysis method used is panel data regression with a fixed-effects model approach. The results of the analysis indicate that ROE has a significant positive impact on stability, while LC and NPL have a significant negative impact. These findings confirm that increased liquidity creation without adequate risk management has the potential to cause financial instability. This study contributes to post-crisis empirical literature and offers policy recommendations to strengthen the resilience of the national banking sector.